Influence of host plant on the mango mealybug, Rastrococcus invadens - Boavida, C.; Neuenschwander, Peter (Wiley, 1995)
Life history traits of the mango mealybug, Rastrococcus invadens Williams, were compared between two neighboring mango trees (Mangifera indica L.), one of which was heavily infested and the other slightly infested. On the infested tree, mealybug survival was high because of good feeding conditions and low escape. The pre‐reproductive period of mealybugs on the heavily infested tree was shorter and total offspring production higher than that of mealybugs on the uninfested tree. This significantly affected the intrinsic rate of natural increase and explained the observed differences in population densities among the trees. The results obtained from an additional experiment using juvenile clones from the same two mango varieties, in which environmental factors were uniform, demonstrated the importance of plant genotype on mealybug size and survival.